The impact of horse purslane (Trianthema portulacastrum L.) infestation on soybean [Glycine max (L.) Merrill] productivity in northern irrigated plains of Pakistan. - Khuram Mubeen; Muhammad Shehzad; Naeem Sarwar; Haseeb Ur Rehman; Tauqeer Ahmad Yasir; Allah Wasaya; Matlob Ahmad; Mubshar Hussain; Muhammad Bilal Abbas; Muhammad Waqas Yonas; Shahid Farooq; Tahani Awad Alahmadi (PLoS ONE, 2021)
Horse purslane (Trianthema portulacstrum L.) is an important weed of soybean crop capable of causing significant yield reduction. Therefore, this study assessed the impact of horse purslane and other weeds' infestation on the productivity of soybean. Ten treatments, i.e., weed-free throughout the growing season, horse purslane-free till 20, 40 and 60 days after emergence (DAE), all weeds-free till 20, 40 and 60 DAE, weedy-check (excluding horse purslane), weedy-check (horse purslane alone) and weedy-check (all weeds) were included in the study. Data relating to density and dry weight of recorded weed species, and yield and related traits of soybean were recorded. Overall, infestation percentage of horse purslane was 33.10 and 51%, whereas dry weight was 12 and 44 g m-2 during 1st and 2nd year, respectively. The highest dry weight of all weed species was recorded at 45 DAE in weedy-check all weeds treatment during both years. The lowest relative density and frequency of horse purslane were recorded in the treatment where it was controlled until 20 DAE during 2018 at 30 DAE, whereas the same treatment recoded the lowest density of horse purslane at 45 DAE during 2019. The relative frequency of horse purslane was non-significant for weedy-check horse purslane and weedy-check all weeds treatments during 2018, whereas former treatment had higher relative frequency of horse purslane in weedy-check all weeds than the later during 2019. Yield and related traits significantly differed among different treatments used in the study. The treatment all weeds controlled until 40 DAE recorded higher number of pods per plant, 1000-seed weight and seed yield during both years. The yield reduction in weedy-check treatments was; weedy-check all weeds > weedy-check all weeds except horse purslane > weedy-check horse purslane only. It is concluded that horse purslane was not the sole weed interfering soybean fields and weed flora consisted of false amaranth [Digera muricata (L.) Mart.] and purple nut sedge (Cyperus rotundus L.). Hence, if the soybean fields in northern irrigated plains of Pakistan are infested with horse purslane or heavily infested with horse purslane or other weeds, these should be controlled in initial 40 DAE to improve soybean productivity.